Treatment strategies for polycythemia vera: Observations in a Dutch "real‐world" cohort study. (5th September 2019) - van de Ree‐Pellikaan, Claire; de Kreuk, Arne; Schaar, Cees G.; Beeker, Aart; Dompeling, Ellen C.; Gerrits, Cees J. H.; van Houten, Anja A.; Schipperus, Martin R.; Strobbe, Leonie; Posthuma, Eduardus F. M.; Klauke, Karin; Westerweel, Peter E.
Abstract: Objectives: Assessment of "real‐world" treatment strategies and outcome in Dutch polycythemia vera (PV) patients. Methods: Retrospective chart review in 150 patients with PV (WHO 2008 diagnostic criteria) from 10 major non‐academic hospitals in the Netherlands. Results: Patients (median age 64 years, 49% male) frequently had cardiovascular risk factors (56%) and prior vascular events (31%). About 70% of patients were high‐risk, based on ELN criteria. However, the majority of patients were treated with phlebotomies alone (55%). Cytoreduction with hydroxyurea (HU) was received by 44% as part of their initial therapy, with or without phlebotomies. The time to achieve the 45% hematocrit target was shortest in patients treated with phlebotomies with or without HU (125 ± 99 and 197 ± 249 days, respectively) compared to patients treated with only HU (232 ± 216 days). Leukocyte and platelet levels were lower in HU‐treated patients, and ELN response targets were more often reached. During the median follow‐up period of 4.1 years, 14 patients (9%) suffered a thrombotic vascular event. Conclusions: In Dutch clinical practice, there is major clinical variation in treatment strategies for PV. Phlebotomizing patients shorten the time to achieve hematocrit control, while HU better controls platelet and leukocyte levels. The thrombotic vascular event rate remains clinically significant.